Las Graves Consecuencias Psicológicas y Sociales que les causan a una Mujer que ha sido Victima Producto de una Violación - Palacios Andrade, Eliana Valeria (2017)
The report of this investigation refers to the incidence of the crime of rape and is framed in the analysis of psychological and social violence, these forms of violence having the highest incidence in Ecuadorian society. The psychological and social consequences resulting from a violation of a woman have a relevant transcendence within the legal context and the rights of freedom, because it directly compromises the sexual and psychological freedom of the people, fundamental rights for the integral development of the And because psychological violence is the sequel or negative effects that is caused in the victim, much more serious than those caused by the violation. Faced with this problem and making a brief compilation of the legal framework and in reviewing the rules of the Code of Criminal Integral in Article 171 I have been able to determine that the punitive regime, the penalties provided for punishing those responsible for these typical behaviors, unlawful and guilty , Are too weak and bear no relation whatsoever to the seriousness of the acts committed by the aggressor and to the psychological and social consequences that the victim has. Because of the aforementioned, my work focuses on the serious psychological and social consequences that occur to the woman as a result of rape, violating the right of freedom and sexual and psychological integrity to the victim, making my proposal viable, so that To amend Article 171 of our criminal law, the Comprehensive Criminal Organic Code.